The acute:chonic workload ratio in relation to injury risk in professional soccer - Malone, S.; Owen, A.; Newton, M.; Mendes, B.; Collins, K. D.; Gabbett, T. J. (Journal of Science and Medicine in Sport, 2017)
Objectives: To examine the association between combined sRPE measures and injury risk in elite professional soccer. Design: Observational cohort study. Methods: Forty-eight professional soccer players (mean ± SD age of 25.3 ± 3.1 yr) from two elite European teams were involved within a one season study. Players completed a test of intermittent-aerobic capacity (Yo-YoIR1) to assess player`s injury risk in relation to intermittent aerobic capacity. Weekly workload measures and time loss injuries were recorded during the entire period. Rolling weekly sums and week-to-week changes in workload were measured, allowing for the calculation of the acute:chronic workload ratio, which was calculated by dividing the acute (1-weekly) and chronic (4-weekly) workloads. All derived workload measures were modelled against injury data using logistic regression. Odds ratios (OR) were reported against a reference group. Results: Players who exerted pre-season 1-weekly loads of =1500 to =2120 AU were at significantly higher risk of injury compared to the reference group of =1500 AU (OR = 1.95, p = 0.006). Players with increased intermittent-aerobic capacity were better able to tolerate increased 1-weekly absolute changes in training load than players with lower fitness levels (OR = 4.52, p = 0.011). Players who exerted in-season acute:chronic workload ratios of >1.00 to < 1.25 (OR = 0.68, p = 0.006) were at significantly lower risk of injury compared to the reference group (=0.85). Conclusions: These findings demonstrate that an acute:chronic workload of between 1.00 and 1.25 is protective for professional soccer players. A higher intermittent-aerobic capacity appears to offer greater injury protection when players are exposed to rapid changes in workload in elite soccer players. Moderate workloads, coupled with moderate-low to moderate-high acute:chronic workload ratios, appear to be protective for professional soccer players.